Atlantoaxial Instability in Down's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The radiographs and clinical evaluations of 90 children with Down's syndrome were reassessed after an interval of 5 years in a study of atlantoaxial instability (AAI) at the Derbyshire Children's Hospital and Infirmary, Derby, UK.